2004
DOI: 10.1002/macp.200300152
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Methyl Methacrylate with Chloro Zirconocene Enolates

Abstract: Summary: The polymerization of methyl methacrylate (MMA) in the presence of the neutral chloro zirconocene enolates, Cp2ZrCl[OC(OMe)CMe2] (1), Me4C2(Cp)2ZrCl[OC(OMe)CMe2] (2), and Me2C(Cp)2ZrCl[OC(OMe)CMe2] (3), was investigated. None of these compounds is catalytically active on its own. They could be activated by adding Ph3CB(C6F5)4 (4); however, only if the initial concentration of enolate is higher than that of the perfluorated phenyl borate. Polymers were produced with a number average molar mass of up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…This mechanistic insight brought about an efficient and living polymerization system at or below 0 °C by simply substituting the slow initiating Cp 2 ZrMe 2 with the preformed neutral zirconocene enolate Cp 2 ZrMe[OC(O t Bu)CMe 2 ]: namely the [Cp 2 ZrMe(THF)] + [BPh 4 ] − /Cp 2 ZrMe[OC(O t Bu)CMe 2 ] pair . Further studies by the groups of Collins and Bandermann showed that neutral ester enolate Cp 2 ZrMe[OC(OR)CMe 2 ] (R = Me, t Bu) is inactive by itself, but its combination with the metallocenium cation Cp 2 ZrMe + as catalyst is highly active and of living characteristics in a bimolecular MMA polymerization process. , Other analogous catalyst/initiator pairs, such as the [Cp 2 ZrCl] + [B(C 6 F 5 ) 4 ] − /Cp 2 ZrCl[OC(OMe)CMe 2 ] pair derived from the proposed complex reaction sequence starting with Cp 2 ZrCl[OC(OMe)CMe 2 ] and [Ph 3 C][B(C 6 F 5 ) 4 ], have also been reported …”
Section: Methacrylate Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanistic insight brought about an efficient and living polymerization system at or below 0 °C by simply substituting the slow initiating Cp 2 ZrMe 2 with the preformed neutral zirconocene enolate Cp 2 ZrMe[OC(O t Bu)CMe 2 ]: namely the [Cp 2 ZrMe(THF)] + [BPh 4 ] − /Cp 2 ZrMe[OC(O t Bu)CMe 2 ] pair . Further studies by the groups of Collins and Bandermann showed that neutral ester enolate Cp 2 ZrMe[OC(OR)CMe 2 ] (R = Me, t Bu) is inactive by itself, but its combination with the metallocenium cation Cp 2 ZrMe + as catalyst is highly active and of living characteristics in a bimolecular MMA polymerization process. , Other analogous catalyst/initiator pairs, such as the [Cp 2 ZrCl] + [B(C 6 F 5 ) 4 ] − /Cp 2 ZrCl[OC(OMe)CMe 2 ] pair derived from the proposed complex reaction sequence starting with Cp 2 ZrCl[OC(OMe)CMe 2 ] and [Ph 3 C][B(C 6 F 5 ) 4 ], have also been reported …”
Section: Methacrylate Polymerizationmentioning
confidence: 99%
“…161,164 Other analogous catalyst/initiator , have also been reported. 165 The initiator/catalyst components have been covalently linked via a robust µ-oxo linkage into a dinuclear enolate zirconocene complex (Scheme 8). 166 The corresponding cationic enolate complex, which consists of both the ester enolate initiator and the cationic zirconocene catalyst sites, can be generated upon treatment with [PhNMe 2 H][B(C 6 F 5 ) 4 ], affording a highly active, controlled polymerization system producing st-PMMA (g80% rr) with high I* (g78%) and TOF (>380 h -1 ) at T p e -20 °C.…”
Section: Nonbridged Catalystsmentioning
confidence: 99%
“…There is increasing interest in the utilization of technologically important, single-site cationic group 4 metallocene catalysts, which have been extensively investigated and successfully employed for the (co)polymerization of nonpolar vinyl monomers (α-olefins in particular), for polymerizations of polar, functionalized vinyl monomers including methacrylates, acrylates, , acrylamides, and methyl vinyl ketone . The polymerization of (meth)acrylates has also been studied computationally. Certain catalyst structures exhibit a high degree of control over polymerization characteristics (activity and efficiency; polymer molecular weight, MW; MW distribution, MWD; livingness) and stereochemistry (polymer tacticity and stereocontrol mechanism), enabling the ambient-temperature synthesis of highly isotactic poly(methacrylate)s (≥95% mm ) ,,,, and poly(acrylamide)s (>99% mm ) using chiral C 2 -ligated zirconocenium complexes as well as highly syndiotactic poly(methacrylate)s (≥94% rr ) using chiral C s -ligated zirconocenium complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the polymerization of polar vinyl monomers with such highly electron-deficient group 4 metallocene and related complexes has been investigated to a much lesser extent . Nonetheless, there is increasing interest in the latter area, with several types of group 4 metallocene complexes being examined for polymerizations of methacrylates, acrylates, , acrylamides, and methyl vinyl ketone . The polymerization of (meth)acrylates has also been studied computationally. Overall, these studies have been focused on the following four major aspects of polymerization: activity/efficiency (catalyst turnover frequency and initiator efficiency), stereospecificity (polymer tacticity and stereocontrol mechanism), control (polymer molecular weight, MW, and molecular weight distribution, MWD, as well as livingness and block copolymer production), and mechanism (kinetics and elementary reactions).…”
Section: Introductionmentioning
confidence: 99%